2008
DOI: 10.1002/rcm.3708
|View full text |Cite
|
Sign up to set email alerts
|

A serum metabolomic investigation on hepatocellular carcinoma patients by chemical derivatization followed by gas chromatography/mass spectrometry

Abstract: The purpose of this study was to investigate the serum metabolic difference between hepatocellular carcinoma (HCC, n = 20) male patients and normal male subjects (n = 20). Serum metabolome was detected through chemical derivatization followed by gas chromatography/mass spectrometry (GC/MS). The acquired GC/MS data was analyzed by stepwise discriminant analysis (SDA) and support vector machine (SVM). The metabolites including butanoic acid, ethanimidic acid, glycerol, L-isoleucine, L-valine, aminomalonic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 59 publications
2
79
0
Order By: Relevance
“…The acquired GC/MS data were analyzed by stepwise discriminant analysis and a support vector machine. 38 The metabolites including butanoic acid, ethanimidic acid, glycerol, L-isoleucine, L-valine, aminomalonic acid, D-erythrose, hexadecanoic acid, octadecanoic acid, and 9,12-octadecadienoic acid in combination with each other gave the strongest segregation between the two groups. By applying these variables, it provided a diagnostic model that could well discriminate between HCC patients and normal subjects, and appears to be a useful tool in the area of HCC diagnosis.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 95%
“…The acquired GC/MS data were analyzed by stepwise discriminant analysis and a support vector machine. 38 The metabolites including butanoic acid, ethanimidic acid, glycerol, L-isoleucine, L-valine, aminomalonic acid, D-erythrose, hexadecanoic acid, octadecanoic acid, and 9,12-octadecadienoic acid in combination with each other gave the strongest segregation between the two groups. By applying these variables, it provided a diagnostic model that could well discriminate between HCC patients and normal subjects, and appears to be a useful tool in the area of HCC diagnosis.…”
Section: Biomarkers and Metabolomics Studies On Hccmentioning
confidence: 95%
“…Nontarget metabolomics approaches have also been used to search for new biomarkers and to explore the mechanism of carcinogenesis in hepatic diseases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). According to these stud-ies, several circulation metabolites have been reported to be predictors for HCC, such as hexanal, 1-octen-3-ol, octane (18), and a combination of multimetabolites (21). Soga et al found that serum ␥-glutamyl dipeptides can be used as biomarkers for discriminating different liver diseases (22).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…The mixture was left to react for 1 h in a microwave oven at 90 °C. After incubation, the samples were again vortex-mixed for 1 min and prepared for GC-MS analysis (Xue et al, 2008).…”
Section: Specimen Processingmentioning
confidence: 99%
“…The mass spectrometer was operated in electron impact (EI) mode (70 eV) and mass was acquired from m/z 45 to m/z 500 at a mass accuracy of 0.1 atomic mass units. The acceleration voltage was turned on after a solvent delay of 6 min (Xue et al, 2008).…”
Section: Gc-ms Analysismentioning
confidence: 99%